Tamanho de amostra para caracteres morfológicos e produtivos de feijão guandu - Facco, Giovani (2014)
The sample size represents the number of plants to be evaluated for an appropriate experimental design. It is assumed that there is variability in the sample size between characters, between evaluation periods and between growing seasons. The objective of this study was: to determine the sample size for morphological and productive characters of pigeonpea (Cajanus cajan) and check for variability in sample size (number of plants) between the evaluation periods and between crop years. Two tests of uniformity (experiments without treatments) were conducted during two growing seasons. In the first growing season, 2011/ 12 crop, the sowing was broadcasted with the second growing season, 2012/13 crop, sowing was done in rows spaced 0.50 m. The floor area in each of the experiments was 1.848 m2 and 360 plants were marked in the central area on a gride 2 m × 2 m. 11 characters (plant height, number of nodes and stem diameter) were evaluated in 13 seasons in the first growing season and 22 times in the second growing season, green the other characters (green mass of root, stem, leaf mass shoot and total dry root, stem, leaf, dry weight of shoot and total dry mass) mass green mass were evaluated in a time each crop year. For each character, descriptive statistics were calculated and verified normality by using the Kolmogorov - Smirnov test, and the randomness Run Test. For each character, we calculated the sample size (η), for semiamplitudes confidence interval (estimation errors) equal to 2, 4, 6, ...,20 % of the estimated mean (m), with a coefficient confidence (1 - α) of 95 %. Η was set at 360 plants, and the estimation error was calculated as a percentage of the estimated mean (m) for each of the characters. There is variability in the sample size between morphological and productive characters of pigeonpea for morphological and productive characters between crop years and morphological characters between the evaluation periods.